ENHANCING COMMUNITY CLINICAL PHARMACY STUDENTS’ RECOUNT WRITING SKILL THROUGH THE “EARTH SONG” VIDEO CLIP AT STIKES WIDYA DHARMA HUSADA TANGERANG - Anggraini Karditiawati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
The study's objectives were to ascertain how the teacher enhanced the recount writing abilities of community clinical pharmacy students at STIKes Widya Dharma Husada Tangerang by having them to watch the